Contribution of aquaculture on livelihood development of fish farmer at Noakhali, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The present study was conducted to assess the contribution of aquaculture on livelihood status of fish farmer at Noakhali sadar upazila. This research work was carried out during the period of February 2013 to July 2013. A total of 50 fish farmers were interviewed with a well-structured questionnaire. The survey revealed that average pond size was 0.48 ha with 40% of the farmers having ponds of single ownership, 20% having ponds of multiple-ownership, 30% having ponds of single lease and 10% having ponds of multiple leases.  Poly culture of Indian major carps and exotic carps has been practiced by most of the farmers. Fish fingerlings were stocked from April to June and average stocking density was 12,370 fingerlings/ha. The average fish production cost was Tk 69,870/ha/yr. Although the living condition of the rural fish farmers were poor, livelihood outcomes were found positive and 88% of the farmers have improved their socio-economic conditions through fish farming. The gross income and net profit were Tk. 1, 06,400 and Tk. 1, 00,000/ha/yr respectively. The average monthly income was in range of BDT 15,000-25,000. Their basic need like food, cloth, house, education and medical facility had changed after fish farming. The households have broadly improved their food consumption, family education, standards of living, purchasing power, choice and economic ability through fish farming. The constraints for sustainable pond fish farming in the areas were lack of technical knowledge of the farmers, disease of fishes, multiple ownership of the pond, higher production cost (mainly seeds and feed), in-sufficient supply of fry and fingerlings, lack of money and credit facilities and inadequate extension services. It is therefore essential to provide the necessary training facilities with institutional and organizational supports, credit facilities and extension services for sustainable fish production and livelihoods of rural fish farmers.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 106-121